Potential applications of landscape ecological patch-gradient maps in nature conservational landscape planning - Csorba, Péter (Acta Geographica Debrecina Landscape & Environment series, 2008)
There are rather limited opportunities for using the results of landscape ecology in practical nature conservation. The reasonS for this are – at least partly – the different scales and frames of the two fields. For more effective cooperation there is an opportunity for landscape ecology to determine patch-gradients that are helpful for nature protection in expanding the living space of endangered species via CORINE land use-pattern in mixed use agricultural areas. Such alternative migration tracks become valuable in places, where landscape ecological corridors and stepping stone places are missing. The method applies the gradient concept of landscape structure of McGarigal and Cushman (2005). Determination of patch-gradients can be a good background material for settlement- and infrastructure planning; and for the elaboration of medium- and long term nature protection concepts or for even general landscape protection strategies as well.